Phylogeny, distribution and time divergence of Fuscoporia (Hymenochaetaceae, Basidiomycota) with the description of a new species from Dhofar region, southern part of Oman - Hussain, Shah; Al-Kharousi, Moza; Al-Muharabi, Marwa A.; Al-Maqbali, Dua’a; Al-Shabibi, Zahra; Al-Balushi, Abdullah H.; Al-Yahya’ei, Mohamed N.; Al Saady, Nadiya; Velazhahan, Rethinasamy; Al-Sadi, Abdullah M. (Phytotaxa, 2022)
Fuscoporia is a large genus with approximately 80 known species, distributed in various climates from subtropical to temperate, across the all continents except Antarctica. Divergence times of Fuscoporia was estimated for the first time, using BEAST v. 1.8.4, with three internal calibration points. Using three DNA regions: internal transcribed spacers (ITS1-5.8S-ITS2 = ITS), D1/D2 domain of large subunit of nuclear ribosomal DNA (28S) and translation elongation factor 1 alpha gene (TEF1α), the ancestral age of the genus was estimated around 77 Myr (million years). Molecular clock analyses also indicate the presence of six major clades, and the stem ages of each were estimated below 50 Myr. These six clades could be used for infrageneric classification of Fuscoporia. Further, we also discussed the distribution of Fuscoporia species in various climates. We hypothesized that the ancestral species of the genus evolved during late Cretaceous period with resupinate fruiting body in subtropics of Southern Asia. Furthermore, we also described a new species in the genus, Fuscoporia dhofarensis from Dhofar region, located in the southern part of Oman. Species description is based on morphological characteristics of fruiting body and phylogenetic analyses of ITS, 28S and TEF1α regions. The new species is characterized by a pileate fruiting body, with dimitic hyphal system, broadly ellipsoid basidiospores.